2005
DOI: 10.1200/jco.2005.02.401
|View full text |Cite
|
Sign up to set email alerts
|

2-(18F)-Fluoro-2-Deoxy-D-Glucose Positron Emission Tomography Detects Clinical Relevant Adenomas of the Colon: A Prospective Study

Abstract: FDG-PET detects colonic adenomas and the diagnostic test characteristics improve with size and grade of dysplasia of the adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 21 publications
5
38
2
4
Order By: Relevance
“…Colon adenoma size and dysplasia grade have been reported to correlate with likelihood of detection by PET-CT. 23 However, a correlation between maximum SUV and colon neoplasm histology has not been demonstrated consistently. Although Gutman et al found that mean SUVs increased with higher grades of dysplasia with highest levels in patients with colon cancers, Israel et al did not observe such a progression in SUV values.…”
Section: Discussionmentioning
confidence: 99%
“…Colon adenoma size and dysplasia grade have been reported to correlate with likelihood of detection by PET-CT. 23 However, a correlation between maximum SUV and colon neoplasm histology has not been demonstrated consistently. Although Gutman et al found that mean SUVs increased with higher grades of dysplasia with highest levels in patients with colon cancers, Israel et al did not observe such a progression in SUV values.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG is actively taken up and accumulates in tumor cells (7). In humans, colorectal adenomas are detected by 18 F-FDG PET to a variable extent depending on adenoma characteristics (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). 18 F-FDG PET in a mouse model of intestinal adenomas has not been reported.…”
mentioning
confidence: 99%
“…The size of the lesion and grade of dysplasia plays a role in the sensitivity. The sensitivity is about 72% for a tumor larger than 1 cm and is about 33% for low grade lesions and 76% for high grade lesions [77,81]. A colonoscopy is warranted when focally increased uptake of FDG is seen in the colon.…”
Section: F-flurodeoxyglucose Positron Emission Tomography (Fdg-pet)mentioning
confidence: 99%
“…Studies have shown that FDG-PET imaging can detect primary carcinomas and premalignant lesions of the large bowel [77][78][79][80][81]. The size of the lesion and grade of dysplasia plays a role in the sensitivity.…”
Section: F-flurodeoxyglucose Positron Emission Tomography (Fdg-pet)mentioning
confidence: 99%